Second Record and DNA Barcode of the Ant Tyrannomyrmex rex Fernández (Hymenoptera: Formicidae: Myrmicinae) - Jacquemin, J. (2017)
Tyrannomyrmex is a rarely collected ant genus from Old World tropical forests comprising only three described species, all of them known from a single worker. Here we report the discovery of a second worker of Tyrannomyrmex rex from a selectively logged primary forest of Singapore, increasing the known distribution range of the species to nearly 250 km South-East. We also provide a DNA barcode for the species and a partial sequence of the wingless gene. Although insufficient evidence prevents us to draw any firm conclusion, the genus seems to be restricted to pristine or relatively undisturbed forests and, as a result, could be highly sensitive to habitat degradation.